City of light (Outcast novels (Keri Arthur), 1, 1, 2016)
The first in an all-new futuristic fantasy series from Keri Arthur—the New York Times   When the bombs that stopped the species war tore holes in the veil between this world and the next, they allowed entry to the Others—demons, wraiths, and death spirits who turned the shadows into their hunting grounds. Now, a hundred years later, humans and shifters alike live in artificially lit cities designed to keep the darkness at bay....   As a déchet—a breed of humanoid super-soldiers almost eradicated by the war—Tiger has spent her life in hiding. But when she risks her life to save a little girl on the outskirts of Central City, she discovers that the child is one of many abducted in broad daylight by a wraith-like being—an impossibility with dangerous implications for everyone on earth.   Because if the light is no longer enough to protect them, nowhere is safe...